Forty Years Since the Epidemic: Modern Paradigms in HIV Diagnosis and Treatment - Patel, Karan (Cureus, 2021)
Human immunodeficiency virus (HIV) is a viral infection that, when transmitted through the exchange of certain bodily fluids, destroys various immune cells and contributes to an overall weakened immune system. If left untreated, HIV progresses to acquired immunodeficiency syndrome (AIDS) - a chronic, life-threatening condition that puts patients at risk for opportunistic infections. Since the emergence of HIV nearly a century ago, the world has seen tremendous advances in elucidating its pathology and progression. These advances have been accompanied by an increased understanding of how subsequent effects and symptoms manifest in afflicted individuals. These discoveries, coupled with the ever-improving technologies and methodologies used for detection and treatment, provide the scientific and medical community with a solid grasp of HIV. Despite this significant headway, there is still much progress to be made; medical advances have allowed people with HIV to manage their disease and live a longer, healthier life, but a definite cure is yet to be found. Thus, the following literature review serves as both an extensive compendium of our current understanding of HIV - its pathology, testing/detection, repercussions, and treatment - and an acknowledgement of the areas that still require further research.